Disorders of the Attention Deficit with Hypertability (ADHD): challenges and possibilities in front of the classroom (Research, Society and Development, 2017)
The present study addresses Attention Deficit Disorder and Hyperactivity Disorder (ADHD), a disorder characterized by its direct influence on the behavior of students and, consequently, on the teaching-learning process, which can generate personal, family and school conflicts. This research had as justification the search for knowledge about ADHD. The general objective of this study was to know and characterize ADHD, comprehending the main challenges and possibilities of pedagogical performance. The methodology used was the bibliographic review. We discuss in this study disorder is becoming more frequent in students in the initial grades, who initially present characteristics such as lack of attention and concentration, restlessness, behaviors, these, which reflect in the school and social life of the student. We have seen that the work of the teacher, with the family, other professionals, and in some cases associated with medication prescribed by a specialized professional is essential to student learning, so that it can perform better in academic activities and in Your personal life. We conclude that the specialized pedagogical approach to children with ADHD becomes essential, but for this it is necessary that the teacher acquainted with this disorder and know the importance of their mediation in the teaching and learning process of this student, providing a service Educational and differentiated education and a work aimed at attending to their specificities, in order to minimize their difficulties.